1999
DOI: 10.1136/gut.44.5.727
|View full text |Cite
|
Sign up to set email alerts
|

Randomised controlled trial shows that glyceryl trinitrate heals anal fissures, higher doses are not more effective, and there is a high recurrence rate

Abstract: Background-Topical application of glyceryl trinitrate (GTN) ointment heals chronic anal fissures, providing an alternative to the traditional first line treatment of surgical sphincterotomy. Aims-To determine the most eVective dose of topical GTN for treatment of chronic anal fissures and to assess long term results. Methods-Seventy consecutive patients with chronic anal fissure, were randomly allocated to eight weeks treatment with placebo, 0.2% GTN three times daily, or GTN starting at 0.2% with weekly 0.1% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
140
5
7

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(159 citation statements)
references
References 21 publications
7
140
5
7
Order By: Relevance
“…Studies showed that oral intake and topical applications of diltiazem reduced the anal pressure significantly. As compared with GTN, diltiazem reported minimal side effects, most of the side effects were facial flushing, mild headache because of changes of negligible diastolic pressure and postural changes of blood pressure, which can be avoided by applying topical diltiazem at bedtime [22,24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies showed that oral intake and topical applications of diltiazem reduced the anal pressure significantly. As compared with GTN, diltiazem reported minimal side effects, most of the side effects were facial flushing, mild headache because of changes of negligible diastolic pressure and postural changes of blood pressure, which can be avoided by applying topical diltiazem at bedtime [22,24].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials show that healing can be achieved in 45-80% patients with GTN therapy, but significant adverse effects such as headache, tachyphylaxis and occasional loss of flatus control have also been reported. Some studies report poor long-term outcome of GTN therapy; only 6% of patients healed in 12 months [10,[20][21][22][23]. Recently, diltiazem has been found efficacious in the treatment of chronic anal fissure.…”
Section: Discussionmentioning
confidence: 99%
“…Associated side-effects were observed in 78% of patients, including headaches in 63% and light-headedness in 52%. Carapeti et al (1999) noted relapse rates of 33% with 0.2% GNT and 25% with escalating-dose GTN (mean followup, 9 months). Headaches were observed in 72% of the patients.…”
Section: Glyceryl Trinitratementioning
confidence: 99%
“…In fact, up to 20% of patients cease GTN therapy due to the severity of their headaches. [30], [31], [32], [33] A 2%GTN ointment applied twice to the anoderm for 6 weeks results in a complete healing in 98% of patients. [6] In another study, Topical diltiazem ointment was used as an agent for chemical sphincterotomy for chronic anal fissure.…”
Section: Topical Nitratesmentioning
confidence: 99%
“…[39] However, recent studies have shown that anal dilation has a higher risk of fissure persistence and higher risk of incontinence. [30] , anal stretch has been scrutinized for causing extensive damage to internal and external sphincters leading to incontinence. A recent randomized controlled trial enrolled 108 patients assigned to anal dilation (AD) versus left lateral sphincterotomy (LLS).…”
Section: Stretching Of Anal Sphincter [Lord's Anal Dilatation]mentioning
confidence: 99%